1912
DOI: 10.5962/bhl.title.42612
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the reproduction and artificial propagation of fresh-water mussels [by] George Lefevre and Winterton Conway Curtis]

Abstract: BULLETIN OF THE BUREAU OF FISHERIES. physical conditions of the waters in which different species thrive and attain their maximum growth, food supply, enemies and diseases, rate of growth and the influence of environmental factors upon it, and the behavior of glochidia and fishes as parasites and hosts, respectively. * * * I have, however, observed on several occasions a violent and sudden reversion of the water currents such as would certainly be fully capable of carrying the eggs forward and into the lattice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(80 citation statements)
references
References 1 publication
(2 reference statements)
3
77
0
Order By: Relevance
“…Owing to the absence of a nervous system the contraction of the adductor muscle may be explained as a tactile response transmitted by the hair tufts, as Pekkarinen & Valovirta (1996) suggested for the glochidium of M. margaritifera. Our observation of a lack of any kind of larval thread in the mature glochidium agrees with Lefevre & Curtis (1912), who, in a study of hookless glochidia, only found larval threads in species of Unio:`we have never seen any sign of such a structure in the ripe glochidia of the other genera which possess hookless glochidia'. Other authors (Schierholz 1889;Conner 1907) have also reported glochidial threads in species of Unio.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Owing to the absence of a nervous system the contraction of the adductor muscle may be explained as a tactile response transmitted by the hair tufts, as Pekkarinen & Valovirta (1996) suggested for the glochidium of M. margaritifera. Our observation of a lack of any kind of larval thread in the mature glochidium agrees with Lefevre & Curtis (1912), who, in a study of hookless glochidia, only found larval threads in species of Unio:`we have never seen any sign of such a structure in the ripe glochidia of the other genera which possess hookless glochidia'. Other authors (Schierholz 1889;Conner 1907) have also reported glochidial threads in species of Unio.…”
Section: Discussionsupporting
confidence: 91%
“…With the exception of M. margaritifera and the vanishing Irish population of the putative species Margaritifera durrovensis (Phillips 1928), there have been no records of living specimens of the other European species Margaritifera auricularia since 1917 (Haas 1917), and no data are available on its host ¢sh, reproduction, development or the morphology of its glochidium. As was supposed by Lefevre & Curtis (1912), with only one exception (see Bauer 1994), the type of glochidium is constant for each genus (Pekkarinen & Englund 1995a) and therefore may be useful for species identi¢cation and classi¢cation (Giusti 1973). However, it has not been described in all species of the genus Margaritifera.…”
Section: Introductionmentioning
confidence: 99%
“…Megalonaias possesses several life history traits that are hypothesized to facilitate parasitism on a taxonomically diverse assemblage of host fish, including broadcasting larvae (Barnhart et al, 2008;Haag, 2012), the ability to encyst on the fins or gills of its hosts (Howard, 1914), and the presence of a larval thread (Lefevre & Curtis, 1912;Howard, 1914;Coker et al, 1921). This suite of life history traits is unusual among amblemines but is common in several other freshwater mussel lineages that also tend to be host generalists (e.g., Unioninae, Hyriidae).…”
Section: Megalonaias Species-level Diversitymentioning
confidence: 99%
“…Fertilized eggs are brooded by the females in modified portions of the gills until the larvae are mature. In the family Unionidae the larvae, termed glochidia, are parasitic, and must attach to a vertebrate host for a period of several weeks (Lefevre and Curtis 1912) in order to metmorphose into juveniles. Unionid mussels can be broadly categorized as either host generalists, which can parasitize a number of different host species, or host specialists which can only parasitize a single host species (Haag and Warren 1997).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%